Multidonor intensive faecal microbiota transplantation for active ulcerative colitis: a randomised placebo-controlled trial. Issue 10075 (25th March 2017) - Paramsothy, Sudarshan; Kamm, Michael A; Kaakoush, Nadeem O; Walsh, Alissa J; van den Bogaerde, Johan; Samuel, Douglas; Leong, Rupert W L; Connor, Susan; Ng, Watson; Paramsothy, Ramesh; Xuan, Wei; Lin, Enmoore; et al.
Summary: Background: The intestinal microbiota is implicated in the pathogenesis of ulcerative colitis. Faecal microbiota transplantation is a novel form of therapeutic microbial manipulation, but its efficacy in ulcerative colitis is uncertain. We aimed to establish the efficacy of intensive-dosing, multidonor, faecal microbiota transplantation in active ulcerative colitis. Methods: We conducted a multicentre, double-blind, randomised, placebo-controlled trial at three hospitals in Australia. We randomly allocated patients with active ulcerative colitis (Mayo score 4–10) in a 1:1 ratio, using a pre-established randomisation list, to either faecal microbiota transplantation or placebo colonoscopic infusion, followed by enemas 5 days per week for 8 weeks. Patients, treating clinicians, and other study staff were unaware of the assigned treatment. Faecal microbiota transplantation enemas were each derived from between three and seven unrelated donors. The primary outcome was steroid-free clinical remission with endoscopic remission or response (Mayo score ≤2, all subscores ≤1, and ≥1 point reduction in endoscopy subscore) at week 8. Analysis was by modified intention-to-treat and included all patients receiving one study dose. We performed 16S rRNA stool analysis to assess associated microbial changes. This trial is registered withClinicalTrials.gov, numberNCT01896635 . The trial has ended; this report presents the final analysis. Findings: From November, 2013, to May, 2015, 85 patients were enrolled to our trial, of whom 42 were randomly assigned faecal microbiota transplantation and 43 were allocated placebo. One patient assigned faecal microbiota transplantation and three allocated placebo did not receive study treatment and were excluded from the analysis. The primary outcome was achieved in 11 (27%) of 41 patients allocated faecal microbiota transplantation versus three (8%) of 40 who were assigned placebo (risk ratio 3·6, 95% CI 1·1–11·9; p=0·021). Adverse events were reported by 32 (78%) of 41 patients allocated faecal microbiota transplantation and 33 (83%) of 40 who were assigned placebo; most were self-limiting gastrointestinal complaints, with no significant difference in number or type of adverse events between treatment groups. Serious adverse events occurred in two patients assigned faecal microbiota transplantation and in one allocated placebo. Microbial diversity increased with and persisted after faecal microbiota transplantation. Several bacterial taxa were associated with clinical outcome; in particular, the presence of Fusobacterium spp was associated with lack of remission. Interpretation: Intensive-dosing, multidonor, faecal microbiota transplantation induces clinical remission and endoscopic improvement in active ulcerative colitis and is associated with distinct microbial changes that relate to outcome. Faecal microbiota transplantation is, thus, a promising new therapeutic option for ulcerative colitis. Future work should focus on precisely defining the optimum treatment intensity and the role of donor–recipient matching based on microbial profiles. Funding: Broad Medical Research Program, Gastroenterological Society of Australia, Mount Sinai (New York) SUCCESS fund, University of New South Wales.